(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This study provides a concise and comprehensive overview of three fundamental components of English phonology: stress, syllable organization, and phonetic transcription. It explains how English stress operates as a phonemic feature that influences meaning, pronunciation, and rhythm through predictable patterns shaped by syllable weight, morphology, and vowel reduction. The discussion of syllable structure highlights the complexity of English phonotactics, including large consonant clusters, open and closed syllables, and the role of syllabic consonants. The section on phonetic transcription emphasizes the importance of the International Phonetic Alphabet (IPA) for accurately representing English sounds, especially in cases of irregular spelling, silent letters, assimilation, elision, and dialectal variation. By examining these three components together, the study demonstrates how stress, syllable formation, and transcription collectively determine the sound system of English and explains why these areas are essential for linguistic research, language teaching, and accurate pronunciation.